Concordance between whole‐exome sequencing and clinical Sanger sequencing: implications for patient care. Issue 5 (10th May 2016) - Hamilton, Alison; Tétreault, Martine; Dyment, David A.; Zou, Ruobing; Kernohan, Kristin; Geraghty, Michael T.; ,; ,; Hartley, Taila; Boycott, Kym M.
Abstract : The direct comparison of 391 coding and intronic variants identified by clinical Sanger sequencing to the whole‐exome sequencing (WES) results of 26 previously undiagnosed patients identified high concordance for well‐covered coding variants, supporting the use of WES as a screening tool for heterogeneous disorders, and highlighting the need for supplementary Sanger sequencing for poorly‐covered genes when the clinical suspicion is high. Importantly, despite remaining difficulties with achieving complete coverage of the whole exome, 10 (38.5%) of the 26 compared patients received a molecular diagnosis through WES. Abstract: The clinical translation of next‐generation sequencing has created a paradigm shift in the diagnostic assessment of individuals with suspected rare genetic diseases. Whole‐exome sequencing (WES) simultaneously examines the majority of the coding portion of the genome and is rapidly becoming accepted as an efficient alternative to clinical Sanger sequencing for diagnosing genetically heterogeneous disorders. Among reports of the clinical and diagnostic utility of WES, few studies to date have directly compared its concordance to Sanger sequencing, which is considered the clinical "gold standard". We performed a direct comparison of 391 coding and noncoding polymorphisms and variants of unknown significance identified by clinical Sanger sequencing to the WES results of 26 patients. Of the 150 well‐covered coding variants identified by Sanger sequencing, 146 (97.3%) were also reported by WES. Nine genes were excluded from the comparison due to consistently low coverage in WES, which might be attributed to the use of older exome capture kits. We performed confirmatory Sanger sequencing of discordant variants; including five variants with discordant bases and four with discordant zygosity. Confirmatory Sanger sequencing supported the original Sanger report for three of the five discordant bases, one was shown to be a false positive supporting the WES data, and one result differed from both the Sanger and WES data. Two of the discordant zygosity results supported Sanger and the other two supported WES data. We report high concordance for well‐covered coding variants, supporting the use of WES as a screening tool for heterogeneous disorders, and recommend the use of supplementary Sanger sequencing for poorly‐covered genes when the clinical suspicion is high. Importantly, despite remaining difficulties with achieving complete coverage of the whole exome, 10 (38.5%) of the 26 compared patients were diagnosed through WES.